A woman among warlords : the extraordinary story of an Afghan who dared to raise her voice - Joya, Malalai; O'Keefe, Derrick (New York : Scribner, 2009)
In the tradition of Ayaan Hirsi Ali's'Infidel,' and also the subject of an award-winning documentary, this impassioned, first-person account tells of a courageous young Afghani woman who risks her life by denouncing the powerful warlords in her country.
Keywords: Joya, Malalai; Afghanistan. -- Ulasi Jirgah -- Biography; Women legislators -- Afghanistan -- Biography; Legislators -- Afghanistan -- Biography; Women -- Afghanistan -- Biography; Afghan War, 2001-; Human rights -- Afghanistan; Democratization -- Afghanistan; Women's rights -- Afghanistan; Afghanistan -- Politics and government -- 2001-